The Division of Madzhab and the Importance of the Role of Usul Fiqh in Uniting Differences - Cantika Dwi Brilliant Putri; Zyl Karimah; Louis Leonardo (Al-Fiqh: Journal of Contemporary Islamic Law, 2026)
This study aims to explore the role of Ushul Fiqh in uniting Islamic schools of thought (mazhab) and resolving sectarian divisions. Sectarian fragmentation among Muslim communities has led to social tensions and conflicts, hindering unity and progress. Despite the importance of Ushul Fiqh in Islamic jurisprudence, its practical application to promote inter-sectarian dialogue and social harmony remains underexplored. Using a library research methodology, this study reviews scholarly documents, fatwas, and empirical studies to understand the theoretical and practical implications of Ushul Fiqh. The findings reveal that Ushul Fiqh can serve as a critical tool for addressing sectarian differences by offering a flexible legal framework for resolving conflicts. However, there is a gap between academic discourse and grassroots application, with limited public engagement and understanding of Ushul Fiqh. Additionally, the frequency and level of participation in Ushul Fiqh discussions are positively correlated with greater community harmony. The study contributes to the existing body of knowledge on Islamic legal traditions and recommends broader public education on Ushul Fiqh to enhance its role in reducing sectarian tensions. Future research should explore the practical implementation of Ushul Fiqh in diverse community contexts.